1998
DOI: 10.1038/emm.1998.9
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ upregulates the stromelysin-1 gene expression by human skin fibroblasts in culture

Abstract: A b s t r a c tThe equilibrium between deposition and degradation of extracellular matrix(ECM) is essential to normal tissue developement and repair of wound or inflammatory responses. It has recently become apparent that several cytokines and growth factors are capable of modulating fibroblast proliferation and biosynthetic activity. To understand the role of these factors in connective tissue regulation, we examined the effect of interferon-( I F N -) on stromelysin-1 gene expres-sion in cultured human derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
2
5
0
Order By: Relevance
“…Such transcription factors are poorly characterized and therefore it is of considerable interest that the promoter of IFI 16, an IFN‐inducible gene, can be regulated through an AP‐1 binding site and that IFNγ can induce binding to AP‐1 sites. This finding confirms other reports that have indicated AP‐1 binding complexes may be transcriptional regulators of IFN‐inducible genes [Lee et al, 1998; Kim et al, 2000] and that increases in expression of fos and Jun family members can be observed following IFN treatment [Rubio, 1997; Der et al, 1998]. Furthermore, signal transduction pathways that lead to activation of AP‐1 binding factors are activated following IFNγ treatment [Liu et al, 1994; Sakatsume et al, 1998; Goh et al, 1999].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such transcription factors are poorly characterized and therefore it is of considerable interest that the promoter of IFI 16, an IFN‐inducible gene, can be regulated through an AP‐1 binding site and that IFNγ can induce binding to AP‐1 sites. This finding confirms other reports that have indicated AP‐1 binding complexes may be transcriptional regulators of IFN‐inducible genes [Lee et al, 1998; Kim et al, 2000] and that increases in expression of fos and Jun family members can be observed following IFN treatment [Rubio, 1997; Der et al, 1998]. Furthermore, signal transduction pathways that lead to activation of AP‐1 binding factors are activated following IFNγ treatment [Liu et al, 1994; Sakatsume et al, 1998; Goh et al, 1999].…”
Section: Discussionsupporting
confidence: 92%
“…Mutation of the IAE rendered the promoter unresponsive to IFNγ treatment, indicating that the AP‐1 site is functional and contributes to IFNγ‐mediated promoter activation. Similar conclusions were reached by those analyzing the regulation of IL‐18 [Kim et al, 2000], and stromelysin‐1 [Lee et al, 1998] promoters. The MAP kinase pathway has been linked to certain biological activities of IFN such as regulation of hematopoiesis, although the molecular mechanisms underlying these effects are unknown [Verma et al, 2002].…”
Section: Discussionmentioning
confidence: 64%
“…As described before for fibroblasts [16] and HSC [17], both MMP-3 and -13 mRNAs are regulated in an opposite manner compared to the profibrogenic transcripts. Thus mRNA expression of MMP-2, a protease that is considered pro-fibrogenic due to its ability to degrade basement membrane collagen [18], a structure that can induce quiescence and inhibit migration of HSC/MF [19], was upregulated in the Mdr2-/-mice at week 4, paralleling their peak profibrogenic activation.…”
Section: Discussionmentioning
confidence: 89%
“…Most studies show that the inflammatory mediators interleukin (IL)‐1β and tumour necrosis factor‐α (TNF‐α) upregulate MMP‐1 protein in human skin fibroblasts (21, 22) and fibroblasts isolated from other tissues (23–25). Monocyte chemoattractant protein‐1 stimulates the production of MMP‐1 protein in human fibroblasts via IL‐1α(26), basic fibroblast growth factor induces synthesis of proMMP‐1 (22) and interferon‐gamma enhances MMP‐3 gene expression (27). Of these mediators, IL‐1 and TNF‐α protein levels are known to be higher in venous ulcer wound fluid than in acute mastectomy wound fluid (28) and decrease as venous ulcers start to heal (29, 30).…”
Section: Discussionmentioning
confidence: 99%